2018
DOI: 10.1056/nejmoa1711460
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Study of Ibalizumab for Multidrug-Resistant HIV-1

Abstract: In patients with MDR HIV-1 infection who had advanced disease and limited treatment options, ibalizumab had significant antiviral activity during a 25-week study. Evidence of the emergence of diminished ibalizumab susceptibility was observed in vitro in patients who had virologic failure. (Funded by the Orphan Products Clinical Trials Grants Program of the Food and Drug Administration and TaiMed Biologics; TMB-301 ClinicalTrials.gov number, NCT02475629 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
172
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(180 citation statements)
references
References 33 publications
5
172
2
1
Order By: Relevance
“…This was the motivation behind the development of ibalizumab, an anti-CD4 monoclonal antibody recently approved by the FDA for use in patients who have failed previous HIV regimens. 30 This is also the reasoning behind continued development of PRO140, an anti-CCR5 monoclonal antibody for use in a similar patient population. 31 Both of these agents are expensive and must be given parenterally, limiting their use to high-income countries.…”
Section: New Drugs New Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the motivation behind the development of ibalizumab, an anti-CD4 monoclonal antibody recently approved by the FDA for use in patients who have failed previous HIV regimens. 30 This is also the reasoning behind continued development of PRO140, an anti-CCR5 monoclonal antibody for use in a similar patient population. 31 Both of these agents are expensive and must be given parenterally, limiting their use to high-income countries.…”
Section: New Drugs New Formulationsmentioning
confidence: 99%
“…First is the concern that more and more infected patients will harbor HIV that is resistant to available drugs. This was the motivation behind the development of ibalizumab, an anti‐CD4 monoclonal antibody recently approved by the FDA for use in patients who have failed previous HIV regimens . This is also the reasoning behind continued development of PRO140, an anti‐CCR5 monoclonal antibody for use in a similar patient population .…”
Section: New Drugs New Formulationsmentioning
confidence: 99%
“…Maintaining FTC in the current regimen may not be necessary, but using agents with partial virologic activity (TAF) is a recommended strategy in MDR HIV . New ARV options for MDR HIV are now available and include ibalizumab or doravirine (based on its unique resistance profile) and could be an option for future ARV simplification …”
Section: What Is New and Conclusionmentioning
confidence: 99%
“…2,22 New ARV options for MDR HIV are now available and include ibalizumab or doravirine (based on its unique resistance profile) and could be an option for future ARV simplification. [23][24][25]…”
Section: What Is Ne W and Con Clus I Onmentioning
confidence: 99%
“…For example, an FDA-approved CCR5 receptor antagonist maraviroc (MVC) is effective to inhibit R5tropic HIV-1 entry into cells [6]. Treatment with the humanized IgG4 monoclonal antibody ibalizuman, which blocks the entry of HIV-1 into cells by noncompetitive binding to CD4, showed that 43% and 50% of patients had a viral load <50 and 200 copies per milliliter, respectively, at week 25 [7]. However, it is unclear which side-effects result from long-term use of HTAs.…”
Section: Introductionmentioning
confidence: 99%